Structural racism as a leading cause of racial disparities in breast cancer quality of care outcomes: a systematic review - Abdelhadi, Ola; Williams, Michelle; Yan, Alice (Frontiers in Oncology, 2025)
BackgroundNon-Hispanic Black women have a disproportionately higher breast cancer mortality rate compared to non-Hispanic white women. Structural racism embedded within societal systems plays a fundamental role in perpetuating these persistent disparities. This systematic review aims to examine the relationship between structural racism and breast cancer quality of care outcomes across various racial and ethnic groups.MethodsFollowing the PRISMA guidelines, we conducted a systematic review of PubMed, Embase, and CINAHL for studies published until October 30, 2024, that examined the relationship between structural racism and breast cancer quality of care outcomes. We employed the Healthy People’s Social Determinants of Health (SDOH) framework to identify structural racism measures within these five themes: economic stability, education access, healthcare access, neighborhood and built environment, and social and community welfare. Breast cancer quality of care outcomes were assessed using the Donabedian quality of care model which encompasses three components of quality: process measures, structural measures, and outcome measures.ResultsWe conducted a systematic review of 262 studies that included at least one measure of structural racism linked to a breast cancer quality of care outcome. Of these, 29 studies met the eligibility criteria for inclusion. The most frequently examined measures of structural racism were those related to residential segregation and redlining, which pertain to neighborhood and built environment SDOH domains. The predominant finding across the studies was that both residential segregation and redlining were significantly associated with adverse breast cancer outcomes. Theses outcomes included higher mortality rates, later-stage diagnoses, and suboptimal treatment. These effects exhibited variability based on race, comorbidity, and neighborhood characteristics, highlighting the complex role of structural racism in perpetuating disparities in breast cancer outcomes.ConclusionThe complex relationship between measures of structural racism and breast cancer quality of care outcomes underscores the necessity for ongoing research to understand the pathways through which structural racism impacts health outcomes. Understanding these pathways is essential for developing targeted interventions and promoting health equity in breast cancer care.